Penerapan Framework Codeigniter Pada Aplikasi Pengenalan Seni Budaya Kota Sumedang (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Indonesia is a country rich in arts and culture, among others culture in Sumedang City. As a good citizen of Indonesia, you should know the culture in this country, don't let our culture be recognized by other nations. At this time the information system has been very advanced. Information system is a system that can provide information to its users. Web-Based Information System for the introduction of cultural arts in the city of Sumedang built using Codeigniter, this system contains articles/news about the arts and culture of the city of Sumedang which were made using Codeigniter, and MySql for database storage. This system will be able to help users to know more about cultural arts in the city of Sumedang, including the art of reak and the renggong horse. The final result obtained is the Application of CodeIgniter in the Sumedang City Cultural Arts Recognition Application, which in general can function properly. Users can get information about the cultural arts of the city of Sumedang, and users can also participate in sharing data that the admin wants to validate.